SAJIAN HIDANGAN GASTRONOMI UPACARA ADAT DALAM SIKLUS KEHIDUPAN MANUSIA JAWA TIMUR - Nurul Farikhatir Rizkiyah; Asrul Bahar; Nugrahani Astuti; Andika Kuncoro Widagdo; Rendra Lebdoyono (LPSDI Bina Patria, 2024)
Food is a symbol of cultural heritage in a certain area where there are values of belief, religion, economy, and social as well as the identity and characteristics of a region. The rich heritage of food is one of the potentials in Indonesia that differentiates it from other countries. Every food served in a traditional ceremony is not spared from the meaning and prayers contained. In preparing, processing and serve traditional dishes, it must be done by a special person who is really given a trust. This study aims to identify and analyze: 1) traditional ceremonies in the human life cycle; and 2) the presentation of gastronomic dishes of traditional ceremonies in East Java. The type of research used is qualitative. This study uses data collection techniques in the form of literature studies, observations, interviews, and documentation in collecting data which is then analyzed using the Miles and Huberman Technique. The results of the study show that: 1) Traditional ceremonies in the human life cycle of East Java consist of 4 types, namely marriage, pregnancy and birth, growth and development, and death); and 2) Gastronomic dishes in traditional ceremonies of the human life cycle consist of 4 types of dishes that are grouped into rice, side dishes, vegetables, and traditional snacks.